2021
DOI: 10.1002/tesq.3063
|View full text |Cite
|
Sign up to set email alerts
|

Transparency with Second Language and Multilingual Transcription

Abstract: Previous methodological discussions in TESOL Quarterly (TQ) discuss imperatives for transparent and reflexive research practices and reporting (Derrick, 2016;Rabbidge, 2017). This article follows these methodological discussions by considering issues in second language (L2) and multilingual transcription by inspecting transcription and analyzing its reporting in empirical contributions to TQ. The study analyzes a series of transparency continuums with transcription reporting in TQ as they pertain to general tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(115 reference statements)
0
3
0
1
Order By: Relevance
“…B. EXMARaLDA und Ähnliches), sondern wir haben es manuell gemacht. Bei der Transkription wurden außersprachliche Merkmale wie Sprechpausen und Gefühlsäußerungen vermerkt, während wir aus Gründen der Übersichtlichkeit und im Einklang mit unseren analytischen Zielen Überschneidungen, kleine, nicht-lexikalische Ausdrücke und Intonation weggelassen haben (Seibert 2021). In den Transkriptionen sind in der Kopfzeile Geschlecht und Geburtsjahr der Gesprächspartner angegeben sowie der Zeitpunkt und der Ort des Interviews.…”
Section: Die Donauschwäbischen Sprachgemeinschaften Von Derunclassified
“…B. EXMARaLDA und Ähnliches), sondern wir haben es manuell gemacht. Bei der Transkription wurden außersprachliche Merkmale wie Sprechpausen und Gefühlsäußerungen vermerkt, während wir aus Gründen der Übersichtlichkeit und im Einklang mit unseren analytischen Zielen Überschneidungen, kleine, nicht-lexikalische Ausdrücke und Intonation weggelassen haben (Seibert 2021). In den Transkriptionen sind in der Kopfzeile Geschlecht und Geburtsjahr der Gesprächspartner angegeben sowie der Zeitpunkt und der Ort des Interviews.…”
Section: Die Donauschwäbischen Sprachgemeinschaften Von Derunclassified
“…Qualitative researchers undertaking research in one language and reporting in another need to understand the ways in which to ensure, and report on, the processes undertaken to ensure the rigor of their work. The transparency of transcriptions is key to demonstrating sound procedural and ethical decision‐making and ensuring quality in research reporting 11 . In reporting on their research, authors should seek to provide specific details of how translations were handled from data collection to reporting.…”
Section: Reflections and Recommendationsmentioning
confidence: 99%
“…9 Al-Amer et al 8 recommend researchers maintain "a trail of atypical words" 8 (p. 1160) encountered, such as local idiosyncrasies, jargon, and slang. It has also been suggested that transparency of translations in research reports could be enhanced by providing participant quotations in the original language as well as in English 11 ; however, this is currently not normal practice in nursing or other health professions. Furthermore, research texts are largely silent on this issue meaning there is little guidance for researchers.…”
Section: Cross-language Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation